Participação social e política de desenvolvimento territorial : a produção de uma sociabilidade estabelecida pelo consenso - Almeida, Luiz Carlos Tavares de (2014)
The main objective that was imposed in this inquiry stripped from the participation of the social actors in Collegiate Territorial of the Western Backwoods of Sergipe and in Municipal Council of Sustainable Development of the local authority of Itabaiana-SE, the interests of a type of development that produces an established sociability are sheared by it pactuação of classes. The query participation has been sponsored in the political scenery as being a significant social profit, while the presuppositions of the democracy participative increased and became a condition of essential mediation. And so, reiterated by the wordy speech of which towards the common interest the differences are dissolved, it finds the pactuação of interests in participation spaces how that of Collegiate Authorities, and of Municipal Councils of Development, average efficient of there is practiced the political "power" inherent in the participation. But, however, this context has been collaborating, in fact, for the production of a condition of politicization of the social struggles, especially, as which the government policies start to have in the market his mediation of excellence, damaging and politicization for conquests you substantivize the struggle, what do not come down to mere reforms or partial conquests. For so much, a spacious bibliographical inquiry was made necessary, of where we weave the bases for a solid theoretical grounding. Parallel and concomitant we lean over the bibliographical revision in documentary inquiries from visits the organs that became necessary during it elapsing of the inquiry. The data collection was carried out from questionnaire techniques with open questions, formal and informal interviews, especially directed to the called local actors , workers, leaders and members of social movements, associations and representatives of the public power. The dialectic was the method that made possible an analysis ruled in the history, in the context, and in the totality of the relations. No separating the extract of the process, of the function and of the form.